2013
DOI: 10.1016/j.bpj.2013.03.061
|View full text |Cite
|
Sign up to set email alerts
|

DNA Ejection from an Archaeal Virus—A Single-Molecule Approach

Abstract: The translocation of genetic material from the viral capsid to the cell is an essential part of the viral infection process. Whether the energetics of this process is driven by the energy stored within the confined nucleic acid or cellular processes pull the genome into the cell has been the subject of discussion. However, in vitro studies of genome ejection have been limited to a few head-tailed bacteriophages with a double-stranded DNA genome. Here we describe a DNA release system that operates in an archaea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 46 publications
2
37
0
Order By: Relevance
“…This slowing down does not occur for configurations that are already significantly disordered and entangled due to the lack of cholesteric interactions. This is well consistent with the recent experiments on the histone His 1 archaeal virus for which both a significant slowdown in kinetics and higher incidence of stalled ejections were observed upon increasing the solution ionic strength (32).…”
Section: Unraveling Dynamics Of Dna Knotssupporting
confidence: 92%
See 1 more Smart Citation
“…This slowing down does not occur for configurations that are already significantly disordered and entangled due to the lack of cholesteric interactions. This is well consistent with the recent experiments on the histone His 1 archaeal virus for which both a significant slowdown in kinetics and higher incidence of stalled ejections were observed upon increasing the solution ionic strength (32).…”
Section: Unraveling Dynamics Of Dna Knotssupporting
confidence: 92%
“…We note, however, that such complicated cases are very much the exception rather than the rule in our results. In fact, less than 5% of the knots get stuck halfway once ejection has started, consistently with the small incidence of stalled ejections seen experimentally (22,32). The nontrivial chain entanglement associated with these configurations is further illustrated by the relatively high internal force that eventually builds up inside the capsid (Fig.…”
Section: Unraveling Dynamics Of Dna Knotssupporting
confidence: 62%
“…Interestingly, a subset of VP21 apparently is modified by lipid moieties, although the lipid bilayer could not be detected by either biochemical or structural approaches (47,48). Furthermore, treatment of His1 virions with various compounds induced the transformation of spindle-shaped particles into tubelike structures which were devoid of the genomic DNA (47,49). It has been suggested that such reorganization is biologically relevant and reflects structural changes accompanying virus entry into the host (47).…”
mentioning
confidence: 99%
“…Importantly, virion flexibility might represent an inherent, biologically relevant property common to all spindle-shaped viruses. It has been demonstrated recently that under certain conditions, virions of halophilic salterprovirus His1 (5,20) and hyperthermophilic virus Pyrococcus abysii virus 1 (PAV1) (2) also undergo structural transformation from regular spindles into elongated particles (2,21,22).…”
mentioning
confidence: 99%